ANALISIS KASUS SENGKETA KEPERDATAAN KEPEMILIKAN TANAH YANG BERSERTIFIKA GANDA (Studi Putusan Pengadilan Negeri Kabanjahe Nomor 30/Pdt.G/2009/PN.Kbj ) - YESICHA CRISTIANITA GINTING (PREMISE LAW JURNAL, 2016)
Etimologically, certificate comes from Dutch “Certificat” which means evidence letter or a clarification letter that proves something. In the Kabanjahe District Court’s Ruling Number 30/Pdt.G/2009/Kbj Ishak Charlie files a complaint on Land Title with good faith in which there are doubled land title certificates with different areas and borders and Ishak Charli claims that he has purchased the land in accordance with the existing procedures. The research type is normative. The research is descriptive analysis. In Kabanjahe District Court’s Ruling Number 30/Pdt.G/2009/Kbj, it is stated that the claim is void due to the incomplete claimed subject so that Ishak Charlie does not obtain justice in his claim despite witnesses and documents that have been proven in the District Court, the certificate possessed by Ishak Charlie has been pronounced annulled before law by State Administrative Court and the valid certificate that is recognized by the State Administrative Court is the one that belongs to Syamsuddin Arifin. Keywords: Civil Dispute over Doubled Land Title Certificates